加入WTO对中国高等教育的影响及对策分析 = Entry into WTO : its impacts in China's higher education and countermeasures - 胡志钢 Hu, Zhi Gang (2008)
Entry into the WTO has grate impact on national economy, trade and development of higher education in China. Specially, opening higher educational market and economic development have brought new changes about talents’ need. This thesis studies strategies to deal with the challenge.